MODEL CIPP DALAM ANALISIS KEBIJAKAN STRUKTURAL DAN PEMBENTUKAN KESADARAN SOSIAL MELALUI PEMBELAJARAN ILMU SOSIAL - Iskandar; Muhammad Mona Adha; Dedy Miswar; Risma Margaretha Sinaga; Irma Lusi Nugraheni (UNDIKMA, 2026)
This study aims to analyse the CIPP (Context, Input, Process, Product) model in explaining the relationship between social, economic and cultural structural policies and the development of pupils’ social awareness through Social Studies (IPS) learning. Unlike previous studies, which generally evaluated Social Studies learning or the implementation of the CIPP model in isolation, this study positions regional structural policies as the primary context, analysed in an integrated manner alongside the inputs, processes and products of learning to explain the formation of students’ social awareness. This study employs a qualitative approach using a descriptive-analytical method, conducted at SMAN 2 Bandar Lampung. Data collection techniques included observation, in-depth interviews and documentation, supported by quantitative data analysis using a Likert scale. The research findings indicate that regional structural policies, as reflected in the Bandar Lampung City Medium-Term Development Plan (RPJMD), serve as the context that shapes pupils’ social conditions. The heterogeneous social structure of schools acts as an input that influences pupils’ learning experiences. The social studies learning process acts as the primary mediator in linking these policies to the development of pupils’ social awareness. Meanwhile, students’ social awareness, as an outcome, falls into the high category, reflecting critical thinking skills, social empathy and active participation. The main findings of this study indicate that structural policies do not directly influence students’ social awareness, but are mediated by contextual and reflective social studies learning. This study makes a theoretical contribution to the development of a public policy-based social studies learning model through the CIPP approach.